Comparison of non-mydriatic fundus photography and optical coherence tomography with dilated fundus examination for detecting diabetic retinopathy including diabetic macular edema - Mae-Lynn Catherine Bastion; NM, Bressler; Norshamsiah Md. Din; Philip GJT; Madhaavi KM; Mohamad Yahya A; Yuhana M (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Given increasing diabetes rates worldwide, better screening tools for diabetic retinopathy (DR) and macular edema (DME) are needed. The study aim was to compare reliability and predictive values between non-mydriatic fundus photography (NMFP) and spectral-domain optical coherence tomography (OCT) for detection of DR and DME with dilated fundus examination (DFE). This was a non-interventional, comparative study. Diabetics underwent both NMFP and macula OCT, followed by DFE. Images were interpreted by two masked ophthalmologists. The DFE result was considered gold standard. One hundred and fifty-four eyes of 83 patients were recruited. Sensitivity of NMFP for DR was 77.3% and 80.3% for OCT. Specificity for NMFP was 81.8% and 55.7% for OCT. Area under Receiver Operating Characteristics Curve (AROC) for DR was 0.80 for NMFP and 0.68 for OCT. The sensitivity of NMFP for DME was 63.2% and 82.5% for OCT. Specificity for DME was 90.1% by NMFP and 61.5% for OCT. Positive predictive value (PPV) of NMFP and OCT for DR was 76.1% (95% CI: 63.9-85.3%) and 57.6% (46.8-67.7%), respectively. Negative predictive value (NPV) of NMFP and OCT was 82.7% (95% CI: 72.8-89.7%) and 79.0% (66.4-87.9%) respectively. Positive predictive value of NMFP and OCT for DME was 80.0% (95% CI: 67.6- 88.5%) and 57.3% (45.9-68.0%), respectively. Negative predictive value of NMFP and OCT was 79.6% (95% CI:70.3 - 86.7%) and 84.8% (95% CI:73.4 - 92.1%), respectively. Eyes with normal OCT miss 21% of DR. In conclusion, NMFP is better than OCT for DR screening, while OCT is better than NMFP and DFE for detection of DME. Both modalities should be for better DR screening.